2019
DOI: 10.1002/app.48473
|View full text |Cite
|
Sign up to set email alerts
|

One pot preparation of polyurethane‐based GSH‐responsive core‐shell nanogels for controlled drug delivery

Abstract: In this work, we present a new type of glutathione (GSH)-responsive polyurethane-based core-shell nanogels (RS-CS-PUNGs) with hydrophilic methoxypolyethylene glycols (mPEG) shell, which was prepared by a one-pot synthetic method. The obtained RS-CS-PUNGs not only show a good size distribution with the hydrodynamic radii around of 20 nm, but also exhibit good stability in the organic solvent. The results demonstrate that GSH (10 mM) trigger the nanogel swelling and accelerate the loaded drug release in PBS (pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Cell experiments confirmed that treatment with DOX-loaded PEG-PU(SS)-PEG micelles significantly inhibited the growth of C6 cells compared with that of other groups [ 38 ]. GSH-responsive PUs were also described in other papers [ 44 , 54 ]. Similarly, reduction-sensitive PUs were synthesized using a disulfide-containing PCL as the hydrophobic block and a cystamine-functionalized PEG as the hydrophilic block [ 40 ].…”
Section: Anti-cancer Drug Delivery Systems Obtained From Biodegradabl...mentioning
confidence: 77%
See 1 more Smart Citation
“…Cell experiments confirmed that treatment with DOX-loaded PEG-PU(SS)-PEG micelles significantly inhibited the growth of C6 cells compared with that of other groups [ 38 ]. GSH-responsive PUs were also described in other papers [ 44 , 54 ]. Similarly, reduction-sensitive PUs were synthesized using a disulfide-containing PCL as the hydrophobic block and a cystamine-functionalized PEG as the hydrophilic block [ 40 ].…”
Section: Anti-cancer Drug Delivery Systems Obtained From Biodegradabl...mentioning
confidence: 77%
“…Biodegradable PU used in PU-DDSs production can be obtained via polyaddition [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] or the polycondensation process [ 69 ]. IPDI, HDI, LDI, CDI, HMDI, and BDI were used as IC components in biodegradable PUs synthesis.…”
Section: Anti-cancer Drug Delivery Systems Obtained From Biodegradabl...mentioning
confidence: 99%
“…It has been revealed that disulfide bond in nanogels could be cleaved by bioreductive GSH and lead to the degradation of nanogels in cells. 40,43 Accordingly, the reductionsensitivity of P(MAA-PMA)-1 nanogels was studied by monitoring the nanogels' size change and the turbidity change over time in response to 10 mM GSH using DLS. As shown in Figure 3a, the relative turbidity of the P(MAA-PMA)-1 nanogels kept decreasing within 6 h either in 10 mM or 20 mM GSH solutions.…”
Section: Ph and Redox Responsive Manner Of P(maa-pma)-1 Nanogelsmentioning
confidence: 99%